La gravitación cubana de la estrella de David - Abreu Veranes, Luis Edel; Pérez Castro, Claudia (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
The development of the Jewish community in Cuba is link by the international context of the contemporary history that stimulates the mobility of the Abraham people to the biggest Caribbean island. This community had an historic point of inflection with the progress of the fascism German regime and the evolution of the Second Word War that impact all it history later.